The ecologic reflexivity in the context of hospital work - Silviamar Camponogara; Flavia Regina Souza Ramos; Ana Lucia Cardoso Kirchhof (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
This article is about a thesis project, which aims to debate the relation between the hospital worker and the present ecologic problematic. The structuring of the object of study comes with the understanding that we live in a "reflexive" society (Giddens, 1997) and that, as social "actors" or characters we present manifestations related to this reflexivity. Also related to this, the ecologic problematic demands from all human beings a responsible behavior concerning the environment (Jonas, 1995). It brings as an aim: to analyze the manifestations of the ecologic reflexivity in the relation of the subjects with their work in a hospital. The research has a qualitative approach, through the strategy of case study, developed in a school-hospital, having as subjects the workers of that institution. The data were collected through a documental analysis and observation as well as a semi-structured interview. The analysis of the data (in progress) will happen with the formation of an analysis corpus and also categorization, with later interpretation in the light of the theoretical referential.